Differences in Perceptual Latency Estimated from Judgments of Temporal Order, Simultaneity and Duration are Inconsistent. (October 2014) - Linares, Daniel; Holcombe, Alex O.
Differences in perceptual latency (Δ L ) for two stimuli, such as an auditory and a visual stimulus, can be estimated from temporal order judgments (TOJ) and simultaneity judgments (ΔJ), but previous research has found evidence that Δ L estimated from these tasks do not coincide. Here, using an auditory and a visual stimulus we confirmed this and further show that Δ L as estimated from duration judgments also does not coincide with Δ L estimated from TOJ or SJ. These inconsistencies suggest that each judgment is subject to different processes that bias 4 L in different ways: TOJ might be affected by sensory interactions, a bias associated with the method of single stimuli and an order difficulty bias; SJ by sensory interactions and an asymmetrical criterion bias; duration judgments by an order duration bias.